2020
DOI: 10.1051/0004-6361/201936754
|View full text |Cite
|
Sign up to set email alerts
|

Gas and dust cooling along the major axis of M 33 (HerM33es)

Abstract: Context. M 33 is a gas rich spiral galaxy of the Local Group. Its vicinity allows us to study its interstellar medium (ISM) on linear scales corresponding to the sizes of individual giant molecular clouds. Aims. We investigate the relationship between the two major gas cooling lines and the total infrared (TIR) dust continuum. Methods. We mapped the emission of gas and dust in M 33 using t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…More recently, Kramer et al (2020) reported an 𝑅 CII OI63 = 0.2 − 20 in M33 with a mean of 4.5 ± 2.6 which matches with the Kaufman et al (2006) one-dimensional uniform density PDR models of 𝑛 H ∼ 2 × 10 2 − 10 4 cm −3 interacting with 𝐺 0 ∼ 1.5 − 60. After experimenting with such simple PDR models, we also confirm the observed ratio of Kramer et al (2020) using 3 -in one-dimensional slabs but we are unable to reproduce this ratio with our full three-dimensional models. We therefore conclude that a ratio between these two lines is rather challenging to use as a diagnostic (see also Kraemer et al 1998).…”
Section: Line Ratiossupporting
confidence: 62%
“…More recently, Kramer et al (2020) reported an 𝑅 CII OI63 = 0.2 − 20 in M33 with a mean of 4.5 ± 2.6 which matches with the Kaufman et al (2006) one-dimensional uniform density PDR models of 𝑛 H ∼ 2 × 10 2 − 10 4 cm −3 interacting with 𝐺 0 ∼ 1.5 − 60. After experimenting with such simple PDR models, we also confirm the observed ratio of Kramer et al (2020) using 3 -in one-dimensional slabs but we are unable to reproduce this ratio with our full three-dimensional models. We therefore conclude that a ratio between these two lines is rather challenging to use as a diagnostic (see also Kraemer et al 1998).…”
Section: Line Ratiossupporting
confidence: 62%
“…This is sufficient to associate most of the [C II] emission with a PDR, start probing the physical conditions around a single H II region, and suggest the presence of CO-dark molecular gas (Braine et al 2012). Based on the comparison of [C II], [O I] and TIR emission with PDR models, Kramer et al (2020) infer a relatively homogeneous medium on these scales in M33, with the large-scale average gas properties being similar to the average of the gas properties measured in four individual regions; namely: a moderate density (n∼2 × 10 2 cm −3 ) and radiation field (G0∼60), with a relatively low beam filling factor of the PDRs, defined as the ratio between the radiation field constrained from the modeling and the radiation field inferred from the observed TIR emission (f b ∼1 by contrast to a larger value enabled by the presence of several PDRs on the line of sight). No difference was detected between the inner and outer parts of the galaxy.…”
Section: Mapping and Velocity Resolved Observations Applied To Galaxiesmentioning
confidence: 99%
“…It is also easily self-absorbed; small amounts of cold foreground gas can absorb [OI]63µm while leaving [OI]146µm unaffected (Liseau et al 2006). This effect has been measured to reduce the [OI]63µm emission by factors of 1.3 ± 1.8 (Kramer et al 2020) up to 2.9 ± 1.6 (Liseau et al 2006). If [OI]63µm/[OI]146µm < 10, [OI]63µm is likely self-absorbed (Díaz-Santos et al 2017;Cormier et al 2015;Tielens & Hollenbach 1985).…”
Section: Also Found Lower [Oi]63µmmentioning
confidence: 99%